ANNALYTICAL BENCHMARKS IN THE WORK “ON A SUN DIAL II” FOR CLARINET B FLAT AND RECITER BY PETRU STOIANOV - Cristian BENCE-MUK (Studia Universitatis Babeş-Bolyai. Musica)
On a sun dial II by Petru Stoianov, for clarinet and reciter strats from Nichita Stănescu’s verses (like many others of the composer’s opuses) and offers sonorous meditation on the poetic text. From a musical point of view, we distinguish an outlook where musical morphology subordinates its syntax through the supremacy of cellular-motivic thinking, with “parsimony of means”. We remark a tight connection between music and the poetic text, both from the point of view of artistic atmosphere and from the perspective of the annalogies and symbols it highlights, unveiling, at the same time, the profound meanings of the literary text.